Obesity management in a Paediatric Emergency Department. Issue 1 (4th April 2014) - Knight, Martin; Booth, Charlotte
Abstract: Increasing numbers of children are either overweight or obese, which has a significant negative impact on their current quality of life and their future health. The results of England's National Child Measurement Programme 2012-13 revealed that approximately one fifth of 4- to 5-year-olds and one third of children aged 10 to 11 years were overweight or obese. Emergency departments (EDs) see large numbers of children every year and therefore represent a potential opportunity to address the obesity issue. A pathway was devised to guide referral of overweight or obese children attending the ED to an existing local healthy living programme. Training sessions on the referral process were provided to ED staff. Audits of ED attendance records were undertaken before and after the implementation of the pathway, and the local programme uptake rate for the first 25 referrals was assessed. Of the first 25 children referred, two (8%) had participated in a programme, six (24%) were on a waiting list, and four (16%) were referred on to services in their local area, giving an overall engagement rate of 48%. Further work needs to be undertaken to increase referrals; however, addressing childhood obesity by accessing existing local services from the ED remains a valuable endeavour.